The Influence of Parent-child Relationship on Prosocial Risk-taking Behavior in Adolescents: Understanding the Chain Mediating Role of Perceived Social Support and Psychological Capital - Li, Xuyang; Ma, Juan (Journal of Educational Research and Policies, 2025)
To explore the influence mechanism of parent-child relationship, perceived social support and psychological capital on adolescents' prosocial risk-taking behavior. The parent-child intimacy scale, prosocial risk-taking behavior scale, perceptive social support scale and psychological capital questionnaire were used to investigate 556 middle school students. The results showed that parent-child relationship was positively correlated with prosocial risk-taking behavior. Perceptive social support and positive psychological capital play a chain mediating role between parent-child relationship and prosocial risk-taking behavior. This study explores the mechanism of parent-child relationship and prosocial risk-taking behavior of adolescents, and the results of this study can provide intervention guidance for promoting the occurrence of prosocial risk-taking behavior of adolescents.